IMPROVING EROSION PROPERTIES OF STEAM TURBINE BLADES VIA SURFACE MODIFICATIONS - Bagcan Kayihan, Agca; Kaya, Cengiz (YILDIZ TECHNICAL UNIV, 2017)
Steam Turbines can generate electricity by using various sources of heat. This is the main reason it is one of the most common type of turbine used in power plants. Steam turbines are composed of various number of stages and each stage is composed of one set of blades. Towards the last stages, water in the steam increases and due to the fact that water velocity is higher than steam velocity, water droplets scatter with the momentum striking at the surface of the turbine blades and causes erosion. Steam turbine blade service life is expected to be not less than 100.000 hours which is approximately 12 years. Blade materials should be considered carefully and necessary surface modifications should be made accordingly. The material is usually selected as martensitic stainless steel due to the service conditions. Steam turbine blades, especially those working in the low pressure region, are subjected to wet steam and their tips are eroded heavily. In this study, a typical low pressure turbine blade material, 1.4021, steel surface has been modified with laser hardening, tungsten carbide coating, and chromium carbide coating. The samples were tested using erosion testing equipment and the results were compared.
Keywords: Steam turbine blades; martensitic steels; HVOF; laser hardening; erosion; Engineering